In Search of Identity: The Contemporary Islamic Communities in Southeast Asia - Noorhaidi Hasan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
The primary objective of this paper is to investigate the contribution of contemporary Islamic movements to the rise of the public sphere in Southeast Asia, particularly in Indonesia and Malaysia. Implicit in this idea of